Challenges in developing MIS – Case from Government sector - Sarveswaran, K.; Perera, P.; Samudaya, N.; Asoka, P.; Fernando, P. (My University, 2006)
Management Information Systems (MISs) are used to manage the processes, people, resources, finance, technologies and services of an organisation. An MIS has been developed continuously since 2007 at the University of Moratuwa based on its Learning Management System implemented in 2003. Currently Examination, Human Resource (HR), Welfare and Finance modules of MISs are online and these modules have contributed to the increase of productivity and efficiency of relevant staff and divisions of the university. Throughout the development, MIS team faced many challenges such as compliance to the government rules and regulations and challenge of convincing end users. The scope of this paper is to share the challenges faced throughout the MIS development, how the problems were handled and the successes of the MIS at the University of Moratuwa. It was identified that the use of Agile model to in-house develop this MIS contributed to the successes.